Aplikasi Ekstrak Wortel (Daucus carota L) Terhadap nilai Overrun, Daya Leleh dan Uji Organoleptik pada Es Krim - Burhan, Hasniar; Mahmud, Andi Tenri Bau Astuti; Yahya, Andi (Anoa: Journal of Animal Husbandry, 2024)
Ice cream with the addition of natural ingredients continues to develop. The natural pigments found in carrots can be used as natural coloring that is safe for making ice cream. The aim of this research is to determine the effect of adding carrots on the quality of ice cream, to determine the effect of adding carrots on the organoleptic value of ice cream. The parameters measured in this research are melting power, overrun and organoleptic test characteristics. The design used was a completely randomized design (CRD) with 4 treatments and 3 replications (0%, 10%, 15% and 20%). The research results show that carrot extract in ice cream can improve taste, color, aroma and preference characteristics. The melting test had a significant effect (0.05) while the Overrun test had a significant effect (0.00). The addition of different carrot extracts caused the texture and aroma of the ice cream to decrease but did not affect the liking value of the ice cream. The addition of carrot extract to P3 (20%) in making carrot ice cream produces the best quality ice cream